Application of adjoint CMAQ chemical transport model in the Athens greater area: sensitivities study on ozone concentrations. (1st January 2011) - Andronopoulos, Spyros; Sfetsos, Athanasios; Vlachogiannis, Diamando; Yiotis, Andreas; Gounaris, Nikolaos
The factors affecting ground level ozone concentrations in the Greater Athens Area (GAA) are examined through adjoint sensitivity analysis, using a meteorology and air quality forecasting system based on MM5, the in-house EMISLAB emissions processing system and the chemical transport model Community Multiscale Air Quality (CMAQ). Sensitivities of the ground level ozone concentrations ('response functional') at certain locations and target times are calculated with respect to the state variables (species concentrations on the grid points and species emissions) by running the adjoint model in reverse mode. The factors affecting ozone levels (most influential regions) are identified through the sensitivities spatial distribution for different times.